How to be an academic superhero : establishing and sustaining a successful career in the social sciences, arts and humanities - Hay, Iain; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2023)
"This thoroughly revised second edition draws on the author's decades of observations and experiences in academia, providing insight and responding to the challenges of fostering a successful academic career. Written in a clear and concise style, the book provides fully updated, forthright and practical counsel on achieving and maintaining a successful, balanced career amidst today's intensifying institutional needs and demands. Iain Hay offers a deep understanding of academic career development from PhD to retirement and in this book addresses a wide range of areas such as writing compelling job applications, handling job offers, academic networking, preserving your public reputation, working with research teams, and how to undertake productive sabbatical leave. The breadth of coverage in this updated book ensures that it will be an excellent resource not only for students and early career academics striving to understand how to establish and cultivate an excellent career path, but also to more senior scholars who are mentoring post graduate students and junior colleagues whilst working to sustain their own careers"--
Contents: 1. Making academic superheroes -- Part I. Setting out as an academic superhero -- 2. Get qualified -- 3. Find a good adviser -- 4. Get mentors; get advice -- 5. Prepare a good CV -- Part II. Refining your academic superhero credentials -- 6. Focus your powers -- 7. Make an early impact -- 8. Get informed and stay current -- 9. Get known and networked -- 10. Learn about local cultures and use 'the system' -- Part III. Applying your academic superpowers where they are needed -- 11. Cultivate high quality referee reports -- 12. Find the right job -- 13. Write a compelling job application -- 14. Perform well at job interviews -- 15. Manage job interview failure and success -- Part IV. Performing as an academic superhero -- 16. Manage your career -- 17. Manage your time -- 18. Publish papers -- 19. Publish a book (or two) -- 20. Speak -- 21. Secure funding -- 22. Attract postgraduate students -- 23. Join or start a research team -- 24. Teach well -- 25. Think about university service and leadership positions -- 26. Find a voluntary role -- 27. Consider consulting -- 28. Get recognized -- Part V. Preserving your academic superpowers -- 29. Review your performance -- 30. Take sabbatical -- 31. Get refreshed -- 32. Sustain collegiality -- 33. Preserve your public reputation -- 34. Stay happy and healthy -- 35. Manage disruptions, interruptions and transitions successfully -- 36. Conclusion: Acknowledging dual strands of success for your academic career -- References -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; College teachers -- Vocational guidance; Scholars -- Vocational guidance